Niches that regulate stem cells and hematopoiesis in adult bone marrow - Comazzetto, Stefano; Shen, Bo; Morrison, Sean J. (Developmental cell, 2021)
In mammals, hematopoietic stem cells (HSCs) engage in hematopoiesis throughout adult life within the bone marrow, where they produce the mature cells necessary to maintain blood cell counts and immune function. In the bone marrow and spleen, HSCs are sustained in perivascular niches (microenvironments) associated with sinusoidal blood vessels—specialized veins found only in hematopoietic tissues. Endothelial cells and perivascular leptin receptor+ stromal cells produce the known factors required to maintain HSCs and many restricted progenitors in the bone marrow. Various other cells synthesize factors that maintain other restricted progenitors or modulate HSC or niche function. Recent studies identified new markers that resolve some of the heterogeneity among stromal cells and refine the localization of restricted progenitor niches. Other recent studies identified ways in which niches regulate HSC function and hematopoiesis beyond growth factors. We summarize the current understanding of hematopoietic niches, review recent progress, and identify important unresolved questions. Hematopoietic stem cells (HSCs) and hematopoietic progenitors are essential for blood production and reside in specialized niches in the adult mammalian bone marrow. In this review, Comazzetto et al. describe our current understanding of HSC and progenitor cell niches, focusing on recent progress and important unresolved questions.